Respuesta :

Answer:

The required location on the gird is shown below.

Step-by-step explanation:

Consider the provided expression.

We need to place the indicated product in the proper location on the grid.

First open the parenthesis as shown:

[tex](a+b-c)(a+b+c)=a(a+b+c)+b(a+b+c)-c(a+b+c)[/tex]

[tex](a+b-c)(a+b+c)=a^2+ab+ac+ab+b^2+bc-ac-bc-c^2[/tex]

Now add the like terms as shown:

[tex](a+b-c)(a+b+c)=a^2+b^2-c^2+2ab[/tex]

Hence, the required location on the gird is [tex](a+b-c)(a+b+c)=a^2+b^2-c^2+2ab[/tex]

ACCESS MORE